Inclusive Supervision: Bridging the Cultural Divide - Victoria Showunmi; Fatima Younas; Leslie Morrison Gutman (Encyclopedia, 2024)
Inclusive supervision is an approach to supervision that prioritizes multicultural competencies and an ethic of inclusion. Inclusivity in doctoral (or PhD) supervision is of key significance due to the collaborative nature of the relationship between supervisors and supervisees. Scant research has been conducted that considers the multiple, intersectional influences and their impact within this relationship. This study employs a rapid review method to synthesize findings on the research evidence encapsulating inclusive doctoral supervision. A search of academic literature spanning the last ten years (2013–2023) led to the inclusion of nine empirical, qualitative research studies on inclusive supervision. A synthesis of the findings resulted in five key challenges to inclusive supervision that diverse students face: power dynamics and feedback, a lack of belonging and support, a racial lens on academic competence, (mis)understandings of cultural differences, and communication and language barriers. In discussing these findings, we employ an intersectional lens and introduce a conceptual framework for an inclusive collaboration between supervisors and supervisees.